Factors associated with difficulty accessing health care for infants in Canada: mothers' reports from the cross-sectional Maternity Experiences Survey. Issue 1 (December 2016) - Brandon, Alisa; Costanian, Christy; El Sayed, Manal; Tamim, Hala
Abstract Background Approximately 13% of Canadian mothers report difficulty accessing health care for their infants, yet little is known about the factors associated with difficulty. Therefore, we examined factors associated with difficulty accessing non-routine health care for Canadian infants, from birth to 14 months of age, as reported by their mothers. Methods Data was drawn from the Maternity Experiences Survey (MES), a cross-sectional, nationally representative survey of mothers who gave birth between November 2005 and May 2006, aged 15 years or older, and lived with their infants at the time of survey administration. A multivariable logistic regression analysis was conducted to determine factors associated with reporting difficulty, with difficulty defined as a mother reporting it being somewhat or very difficult to access a health care provider. Results Analysis of 2832 mothers who reported needing to access a health care provider for their infant for a non-routine visit found that 13% reported difficulty accessing a provider. Factors associated with reporting difficulty were: residing in Quebec (aOR 1.89, 95% CI: 1.31–2.73), being an immigrant (aOR 1.58, 95% CI: 1.10–2.27), mistimed pregnancy (aOR 1.44, 95% CI: 1.05–1.98), low level of social support (aOR 1.69, 95% CI: 1.05–2.73), good health (aOR 1.88, 95% CI: 1.43–2.47), postpartum depression symptoms (aOR 1.55, 95% CI: 1.02–2.37) and a self-reported 'too-short' postpartum hospital stay (aOR 1.69, 95% CI: 1.21–2.35). Additionally, accessing care for an infant with a birth weight of 2500 g or more (aOR 2.43, 95% CI: 1.02–5.82), was associated with reporting difficulty. Household income, mothers' level of education, marital status, Aboriginal ethnicity, and size of community of residence were not associated with difficulty accessing care. Conclusions Ease of health care access for Canadian infants is not equal, suggesting that efforts to improve access should be tailored to groups facing increased difficulties.